Factors Associated With Leftover Food For Inpatients at a General Hospital: A Cross-sectional Study - Misini, Misini; Kustiani, Ai; Astuti, Dwi Woro (STIKes Al-Ma'arif Baturaja, 2025)
Leftover food among inpatients is an important indicator of hospital nutrition service quality, directly impacting nutritional intake and therapeutic effectiveness. High rates of leftover food, particularly in class III patients, highlight the need for an evaluation of factors influencing food consumption. This study aimed to analyze the factors associated with leftover regular meals among class III inpatients at Dr. Hi. Abdul Moeloek General Hospital, Lampung Province. An analytical cross-sectional study was conducted involving 74 class III inpatients. Data were collected through structured interviews and direct observation, and analyzed using bivariate analysis with the Chi-square test. The findings revealed significant associations between food taste (p = 0.000), food appearance (p = 0.047), and outside food consumption (p = 0.011) with patient food leftovers. These three factors were shown to influence the amount of food waste. Good taste and appealing food appearance reduced leftovers, whereas consuming food from outside increased them. Hospitals should improve the sensory quality and presentation of meals and enhance nutrition education for patients and their families to minimize outside food consumption and improve the effectiveness of clinical nutrition services.